Preliminary Studies on Existing Scenario of Selected Soil Property in Cheddikulam DS Division Vavuniya, Sri Lanka - Aashifa, M.A. R.; Loganathan, P. (International Journal of Environment, 2017)
This study was conducted to quantify the spatial variability of soil properties, use this information to produce accurate map by means of ordinary kriging and find the ways to reclaim the problem soil and make suggestions to cultivate the crop variety which is suitable for the existing soil property.70 sampling points were selected for that research using stratified random sampling method. Stratification was based on the type of land cover, and following land cover patterns were identified forest patches, agriculture land patches, grass land patches and catchments. Sampling points were randomly selected from each land cover types. Minimum distance between two adjacent sampling points was 500m. Soil samples were analyzed for pH, EC, exchangeable K, available P. In each location, soils were collected from top to - 30 cm depth (root zone) using a core sampler and sub soil samples were collected around the geo-reference point to obtain a composite sample. Geostatistical tool of the software (ArcGIS 10.2.2. trail version) was used to construct semi-variograms and spatial structure analysis for the variables. Geostatistical estimation had done by kriging. 13% of agriculture land area was acidic soil and 5.7% alkaline soil. 13% of agriculture land area was identified as saline soil. 67.11% of agriculture lands contain more phosphorous concentration than the optimum range. 3.4% agriculture lands contain higher potassium concentration than the optimum range. 98% of forest lands and 100% of grass lands contains phosphorous concentration higher than the optimum range. But forest lands and catchments shows lower level of potassium concentration. 22% of grass lands contain higher potassium than the optimum level. Agriculture practices leads to change in the soil hence identified soil problems should be reclaimed in order to maintain the fertility of soil for sustainable production. Proper management of soil can be a better solution for supporting the successful agricultural activity of community in future and socio-economic development of this region. INTERNATIONAL JOURNAL OF ENVIRONMENT Volume-5, Issue-4, Sep-Nov 2016, page : 1-11